Application of data mining in transportation geotechnics - Correia, A. Gomes (2012)
This paper presents a brief overview of Data Mining applications in transporta- tion geotechnics, highlighting the current research directions and the discussion of some issues that need further attention in the future, mainly related with pre- diction capacities. Some practical applications to earthworks, compaction and pavement engineering are presented to illustrate the capacity of this numerical tool, as well as more advanced techniques illustrated through the development of a predictive model for mechanical behavior of jet grouting material.